Transparansi Tata Kelola Keuangan Di Badan Amil Zakat Nasional (Baznas) Kabupaten Enrekang - Siti Nurahmah Juli; Muchlas M Tahir; Hamrun Hamrun (Publik : (Jurnal Ilmu Administrasi), 2016)
This article discucces the transpararency of financial governance in the national agency Tithe (BAZNAS) Regency Enrekang and to determine the factors that affecct the relazation of the transparency of the financial governance at the national tithe (BAZNAS) Regency Enrekang. This research approach is qualitative, data collection is done using interviews wiith how to choose informants for probability sampling. Data collcted from interviews, then analyzed based on the indicator the asssessment of financial transparency and further elaborated the factors that affect the realization of the transparency financial governance in the Agency tithe natioanl (BAZNAS) Regency Enrekang, and explain tfe factors that influence the realization of financialgovernance in the Natioal tithe (BAZNAS) Regency Enrekang. This research apporoach is qualitative data collection is done using interview with how to choose infprmant by probability sampling, data collected from interview mode and then analyzed using indicators of valuatio indicators financial transparancy and furthur elaborated factors that affect the realization of transprancy financial governance in the Agency tithe Natioanl (BAZNAS). This research shows that there is information disclosure and resposibility from the local governance to convey the development of financial governance in the agency tithe National (BAZNAS) which became a container the distribution of zakat in te district of Enrekang Artikel ini mendiskusikan tentang transparansi tata kelola keuangan pada badan amil zakat asional (BAZNAS) Kabupaten Enrekang. Dan untuk mengetahui faktor faktor yang mempengaruhi terwujudnya tata kelola keunagan pada Badan Amil Zakat Nasional (BAZNAS) Di Kabupaten Enrekang. Pendekatan penelitian ini yaitu kualitatif, pengumpulan data dilakukan menggunakan wawancara dengan cara memilih informan secara probability sampling. Data dikumpulkan dari cara wawancara, kemudian dianalisa menggunakan indikator indakator penilaian transparansi keuangan dan selanjutnya diuraikan faktor faktor yang mempengaruhi terwujudnya transparansi tata kelola keuangan pada badan amil zakat (BAZNAS) Kabupaten Enrekang. Hasil penelitian ini menunjukkan bahwa adanya keterbukaan informasi dan tanggungjawab dari pemerintah setempat untuk menyampaikan perkembangan tata kelola keuangan di BAZNAS Kabupaten Enrekang baik itu melalui web resmi BAZNAS juga rutin setiap bulan di umumkan di setiap kecamtan yang ada di Kabupaten Enrekang. Penelitian ini menunjukkan bahwa adanya sejumlah program yang di adakan BAZNAS yang menjadi wadah dalam pendistribusian zakat yang ada di Kabupaten Enrekang